The Influence of Online Food Delivery Services and Prices on Increasing Turn of Sales on Culinary Business: Case Study on Go-Food - Muhammad Reynaldi; Mustafa Kamal (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2022)
This study aims to examine the effect of online food delivery services and prices on increasing sales turnover of culinary businesses in Kemang District, Bogor Regency. This research is a quantitative study with a population of Go-jek partner culinary businesses in Kemang District, Bogor Regency. The sampling technique in this study used a purposive sampling technique . The number of samples is 100 culinary entrepreneurs who partner with Gofood in Kemang District, Bogor Regency. The research data were analyzed using PLS-SEM (Patial Least Square – Structural Equation Modeling) with SmartPLS software. The results of this study indicate that online food delivery services and prices have a significant effect on increasing sales turnover of culinary businesses in Kemang District, Bogor Regency. So it can be concluded that culinary business people in Kemang District, Bogor Regency need to pay attention to online food delivery services and prices as factors that result in an increase in sales turnover. ABSTRAKPenelitian ini bertujuan untuk meneliti pengaruh layanan online food delivery dan harga terhadap peningkatan omzet penjualan bisnis kuliner di Kecamatan Kemang Kabupaten Bogor. Penelitian ini merupakan penelitian kuantitatif dengan populasi bisnis kuliner mitra Go-jek di Kecamatan Kemang Kabupaten Bogor. Teknik pengambilan sampel pada penelitian ini menggunakan teknik purposive sampling. Jumlah sampel sebanyak 100 pengusaha kuliner yang bermitra dengan Gofood di Kecamatan Kemang Kabupaten Bogor. Data penelitian dianalisis menggunakan PLS-SEM (Patial Least Square – Structural Equation Modeling) dengan perangkat lunak SmartPLS. Hasil penelitian ini menunjukan bahwa layanan online food delivery dan harga memiliki pengaruh yang positif dan signifikan terhadap Peningkatan Omzet penjualan bisnis kuliner di Kecamatan Kemang Kabupaten Bogor. Maka dapat disimpulkan bahwa pelaku bisnis kuliner di Kecamatan Kemang Kabupaten Bogor perlu memperhatikan layanan online food delivery dan harga sebagai faktor yang mengakibatkan peningkatan omzet penjualan. Kata kunci: Go-food, Harga, Layanan Online Food Delivery, Omzet Penjualan Bisnis.